A Study of Relationship Marketing in Chinese Retail market - Xue, Qiusha (2007)
Relationship Marketing, as a new marketing paradigm, has stimulated considerable interests in both the business and the academic world in recent years. It has been believed that companies can achieve success in the long run by maintaining relationships with their customers and business associates. However, the most of the research on relationship marketing focuses on the Western perspectives, and the current literature on relationship marketing in the Asian retail sector is relatively under-researched. Therefore, the aim of this research is to provide some insight into relationship marketing in this sector and country. It seeks to unravel the nature of relationship marketing applied in Chinese retail market, its benefits and key factors of relationship marketing implementation.